Unveiling the occurrence and role of Methylobacterium endophytes in olive trees: insights into potential interactions with Xylella fastidiosa subsp. pauca - Mariangela Carlucci; Pompea Gabriella Lucchese; Cinzia Benincasa; Rosa Nicoletti; Andrea Pacifico; Enzo Perri; Franco Nigro (Chemical and Biological Technologies in Agriculture)
Abstract Background Olive quick decline syndrome (OQDS), caused by Xylella fastidiosa subsp. pauca (Xfp), is a destructive vascular disease affecting olive trees, particularly in Apulia, Southeastern Italy. Control measures rely on containment and replanting with resistant cultivars. Endophytic bacteria, including Methylobacterium spp., have shown potential in mitigating vascular diseases. These facultative methylotrophic bacteria inhabit xylem vessels and compete with pathogens like Xfp by producing siderophores that limit iron availability. Results Analysis of endophytic bacterial populations in olive trees identified Methylobacterium spp. in both healthy and Xfp-infected plants, with variable isolation frequencies. Molecular identification based on 16S rDNA and mxaF gene sequences classified isolates as M. radiotolerans (70%) and M. mesophilicum (30%). Phylogenetic analysis showed limited genetic variation, clustering isolates with reference strains. In vitro experiments revealed that culture supernatants from Methylobacterium spp., grown in siderophore-inducing media, affected Xfp growth in a concentration-dependent manner. At low concentrations (up to 2%), supernatants stimulated Xfp growth, while higher concentrations (20% and 50%) inhibited growth. Selected strains of M. radiotolerans and M. mesophilicum were confirmed as siderophore producers through CAS blue agar tests and targeted LC–MS/MS analysis. LC–MS/MS identified ferrioxamine E and ferrichrome in all Methylobacterium strains, with the highest levels in M. organophilum and M. aminovorans. Deferoxamine was absent, whereas Xfp exhibited elevated production of ferrioxamine E, deferoxamine, and ferrichrome. Conclusions This study underscores the biocontrol potential of Methylobacterium spp. against Xfp, suggesting an ability to compete with the pathogen through siderophore-mediated mechanisms. The dual effect of Methylobacterium supernatants—stimulatory at low concentrations and inhibitory at higher levels—highlights the complexity of plant–microbe–pathogen interactions. The production of ferrioxamine E and ferrichrome suggests a possible role in modulating iron availability in vivo, potentially reducing Xfp's growth and virulence. These findings provide a basis for developing Methylobacterium spp. as sustainable biocontrol agents to manage Xfp in olive production systems. Graphical Abstract